PENGARUH PENERAPAN METODE AIDA (Attention, Interest, Desire, Action) TERHADAP MINAT BELI KONSUMEN DI SHOPEE - yasmir yasmir; Ariyanto M; Imam Prasetyo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to find out whether there is an influence between AIDA (Attention, Interest, Desire, Action) on consumer buying interest at Shopee. The research method used in this research is a quantitative method. The population in this study are Shopee users, while the sample required in this research is 160 Shopee user respondents, with the sampling method being incidental sampling. Next, data processing uses multiple linear regression analysis using the SPSS version 21 program. The results of the t test for the Attention variable (X1) t count are 2.480 > t table 1.975, this is reinforced by a significance value of 0.00 < 0.05, so Attention has a significant effect on buying interest. Interest (X2) t count is 8.909 > t table 1.975 with a significance value of 0.00 < 0.05, so Interest has a significant effect on buying interest. Desire (X3) has a t count of 1.420 < t table 1.975, with a significance value of 0.00 < 0.05, so Desire has no significant effect on buying interest. Action (X4) has a calculated t value of 6.267 > t table 1.975, with a significance value of 0.00 < 0.05, so Desire has a significant effect on buying interest. Based on the f test calculation, the value obtained is 37.426 > from f table 2.43, reinforced by a significance value of 0.00 < 0.05, meaning it is accepted, so it can be concluded that AIDA (Attention, Interest, Desire, Action) together or Simultaneous influence on buying interest.